Pengaruh Intangible Asset Terhadap Firm Value Melalui Financial Policy Dan Financial Performance Pada Industri Manufaktur Di Indonesia - Wibisono, Hermawan; Susilawati, Cicilia Erna; Sunarjanto, Agus (Kajian Ilmiah Mahasiswa Manajemen, 2017)
The purpose of this research was to examine the impact of intangible asset to firm value trough financial policy and financial performance in manufacturing industry in Indonesia. This research is a casual which use financial report as the base of data. This type of method is purposive sampling. The secondary data collected from yearly financial report of manufacturing industry which listed in Jakarta Stock Exchange (JKSE) during 2012-2015. Thi research was analyzing by path analysis method with Software Eviews 7, Microsoft Excel, and SPSS 13. The result of this research shows some results like the result that found that intangible asset has a significant influence to financial policy which represented by debt to equity ratio. This research also found that intangible asset has a significant influence to financial performance which represented by liquidity ratio, return on asset, and asset turnover. This research also found that intangible asset, financial policy which represented by debt to equity ratio and financial performance which represented by return on asset and asset turnover have significant influence to firm value. This research also found that intangible asset has a significant influence to firm value trough financial policy which represented by debt to equity ratio and financial performance which represented by return on asset and asset turnover. Based on this research, the researcher recommend to the investors, firm managerial and the shareholders to take a pay attention the existence of intangible asset in a firm that can be influenced to firm value directly or indirectly trough financial policy and financial performance.